Characterisation of nanoparticles resulting from different braking behaviours. (19th July 2010) - Perrenoud, Alain; Gasser, Michael; Rothen-Rutishauser, Barbara; Gehr, Peter; , Michael Riediker
Brake wear particulate matter (PM) may provoke cardiovascular effects. A system was developed to expose cells to airborne PM from brakes. Six car models were tested, each with full stop and normal deceleration. PM numbers, mass and surface, metals, and carbon compounds were measured. Full stop produced higher PM number and mass concentrations than normal deceleration (up to 10 million particles/cm³ in 0.2 m³ volume). 87% of the PM mass was in the fine (100 nm to 2.5 μm) and 12% in the coarse (2.5 to 10 μm) fraction, whereas 74% of the PM number was nanoscaled (ultrafine < 0.1 μm) and 26% fine PM. Elemental concentrations were 2, 364, 236, and 18 μg/m³ of iron, copper and manganese, respectively, and 664 and 36 μg/m³ of organic and elemental carbon. PM-release differed between cars and braking behaviour. Temperature and humidity were stable. In conclusion, the established system seems feasible for exposing cell cultures to brake wear PM.